2017
DOI: 10.1186/s12610-017-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Semenogelins bound to human sperm and other semen parameters and pregnancy outcomes

Abstract: BackgroundSemenogelins (SEMGs) are major components of human seminal vesicle secretions. Due to SEMG’s sperm-motility inhibitor, a significant negative correlation between sperm motility and the proportion of SEMG-bound spermatozoa (SEMG+) was found in asthenozoospermic patients. SEMGs also show intrinsic inhibitory capability for sperm capacitation; however, studies on actual clinical specimens have not been conducted.MethodsTo reveal the relationship between SEMGs and the fertilizing capacity of sperm from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Seminal vesicles are believed to be responsible for the release of these decapacitating molecules that bind to the sperm membrane to inhibit capacitation. However, this phenomenon has been observed only in human and mice in vitro experiments that mixed capacitated spermatozoa with SP or candidate decapacitation factors [68][69][70]. In the pig, in vivo studies suggest that SP proteins are potentially involved in regulating sperm fertility [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Seminal vesicles are believed to be responsible for the release of these decapacitating molecules that bind to the sperm membrane to inhibit capacitation. However, this phenomenon has been observed only in human and mice in vitro experiments that mixed capacitated spermatozoa with SP or candidate decapacitation factors [68][69][70]. In the pig, in vivo studies suggest that SP proteins are potentially involved in regulating sperm fertility [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a study by Yamakasi et al. [ 12 ] also indicated that patients with higher number of SEMG-unbound spermatozoa can achieve successful pregnancy, making total SEMG-unbound sperm count a relevant parameter for in vivo fertilization. Additionally, SEMG peptides are also involved in other biological functions such as increasing sperm hyaluronidase activity [ 13 ], antibacterial activity [ 14 ], hyperpolarization, and permeability of sperm plasma membrane [ 15 ].…”
Section: Seminal Plasmamentioning
confidence: 99%
“…In Chinese–Han male population, the SEMG1 variant rs2301366 was associated with abnormal semen parameters such as semen volume, sperm concentration, sperm number per ejaculate, and sperm motility and more susceptible to infertility [ 63 ]. In another study, a negative correlation between sperm motility and the proportion of SPMI (of SEMG sequence)-bound spermatozoa was also found in male subjects including infertile normozoospermics, asthenozoospermics, and oligozoospermics [ 12 ]. These findings suggest that SEMGs remained on the sperm surface post-liquefaction might account for impaired sperm motility in infertile men.…”
Section: Factors Affecting Semen Liquefactionmentioning
confidence: 99%
“…Although the mechanism of acceptance of SEMGs has not been fully elucidated, binding of SEMG1 to sperm via adaptor protein EPPIN has been shown [22,23]. Moreover, the SEMG-unbound sperm count is expected to be a relevant parameter for in vivo fertilization based on clinical studies on infertile couples using assisted reproductive technology [24].…”
Section: Introductionmentioning
confidence: 99%